2023
DOI: 10.1037/emo0001222
|View full text |Cite
|
Sign up to set email alerts
|

Silencing screaming with screens: The longitudinal relationship between media emotion regulation processes and children's emotional reactivity, emotional knowledge, and empathy.

Abstract: Many parents use screens to regulate their young children's emotions. We know very little, however, about how this parenting practice is related to the development of emotional competencies (i.e., emotional reactivity, emotion knowledge, and empathy) over time. The current longitudinal study examined bidirectional associations between media emotion regulation and various emotional competencies across a 1-year period during early childhood (between ages 3.5 and 4.5 on average). Participants included 269 child/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…A similar result was reported with reactivity, a sub-dimension of negative affect, defined as the degree to which a person reacts physiologically and behaviorally to the environment. This study with children between three and five showed a positive relationship between children's reactivity and media emotion regulation; children with high reactivity experience media emotion regulation more frequently (Coyne et al 2023).…”
Section: Children's Temperamentmentioning
confidence: 58%
See 4 more Smart Citations
“…A similar result was reported with reactivity, a sub-dimension of negative affect, defined as the degree to which a person reacts physiologically and behaviorally to the environment. This study with children between three and five showed a positive relationship between children's reactivity and media emotion regulation; children with high reactivity experience media emotion regulation more frequently (Coyne et al 2023).…”
Section: Children's Temperamentmentioning
confidence: 58%
“…This scale, which has demonstrated sufficient reliability across various studies, includes items such as "How often do you pass your child your phone or other media device when your child gets fussy while driving somewhere in the car? (Coyne et al 2021(Coyne et al , 2023.…”
Section: Media Emotion Regulationmentioning
confidence: 99%
See 3 more Smart Citations